2021
DOI: 10.1002/ijc.33688
|View full text |Cite
|
Sign up to set email alerts
|

Geophagia and risk of squamous cell esophageal cancer in the African esophageal cancer corridor: Findings from the ESCCAPE multicountry case‐control studies

Abstract: Geophagia, the intentional practice of consuming soil, occurs across the African esophageal cancer corridor, particularly during pregnancy. We investigated whether this practice is linked to endemic esophageal squamous cell carcinoma (ESCC) in this region. We conducted ESCC case-control studies in Tanzania, Malawi and Kenya. Cases were patients with incident histologically/clinically confirmed ESCC and controls were hospital patients/visitors without digestive diseases. Participants were asked if they had ever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…A case study conducted in Tanzania, Malawi, and Kenya showed that geophagia was a common practice in women: 49% in Malawi, 43% in Kenya, and 29% in Tanzania. Whereas in men, the practice of geophagia was significantly lower: 10% in Malawi and up to 1% in Kenya and Tanzania [ 105 ]. The practice of soil consumption has been described in Nigeria and Ghana, where it is associated with efforts to alleviate the symptoms of morning sickness in pregnant women [ 101 , 106 ].…”
Section: Geophagiamentioning
confidence: 99%
“…A case study conducted in Tanzania, Malawi, and Kenya showed that geophagia was a common practice in women: 49% in Malawi, 43% in Kenya, and 29% in Tanzania. Whereas in men, the practice of geophagia was significantly lower: 10% in Malawi and up to 1% in Kenya and Tanzania [ 105 ]. The practice of soil consumption has been described in Nigeria and Ghana, where it is associated with efforts to alleviate the symptoms of morning sickness in pregnant women [ 101 , 106 ].…”
Section: Geophagiamentioning
confidence: 99%
“…A Zambian study reported no association between geophagia and ESCC. In a multicenter case control study (Tanzania, Malawi, Kenya) and the most comprehensive study on ESCC and geophagia thus far, non-significant increase in ESCC risk (OR 1.66; 0.77–3.55 95%CI) was reported in Tanzanian women who consumed soil during pregnancy and regularly [ 69 ]. Results from Malawi and Tanzania did not show a significant association between women who consumed soil during pregnancy or regularly, and ESCC development.…”
Section: Resultsmentioning
confidence: 99%
“…Jorgensen N et al constataram em seu estudo que a regulação da resposta imunológica nos seres humanos depende, entre outros fatores, da atuação das células T reguladoras (TRegs), Brazilian Journal of Health Review, Curitiba, v. 6, n. 6, p.27780-27789, nov./dec., 2023 as quais modulam a intensidade das respostas imunes, seja direcionando a resposta contra diferentes patógenos e tumores, seja restringindo aberrantes respostas inflamatórias desproporcionais. Na gestação, os mecanismos responsáveis pela indução da tolerância imunológica são os mesmos envolvidos no controle das respostas inflamatórias, além de serem também os responsáveis por criar um ambiente pró-tumor.…”
Section: Revisão Bibliográficaunclassified